Leadership Styles in Management - Syahlan, Fatra; Sobandi, A; Santoso, Budi (Eastasouth Institute, 2024)
Leadership plays an increasingly critical role in organizational success, especially in today's rapidly evolving business landscape, where agility and adaptability are paramount. Various leadership styles have garnered considerable attention in management research, reflecting the quest to optimize organizational performance amidst dynamic challenges. Understanding these styles is not merely advantageous but urgent for leaders and management practitioners, as the choice of leadership approach significantly shapes organizational culture, influences employee performance, and ultimately determines the achievement of shared objectives. This study delves into the plethora of leadership styles through an exhaustive examination of management literature, aiming to unveil the multifaceted impact of these styles on organizational performance. The findings of this research endeavour are poised to offer invaluable insights, enriching comprehension of the pivotal role and relevance of leadership styles within management frameworks, while also laying the groundwork for future explorations in the realm of organizational leadership and management.